Environmental ototoxicants, a potential new class of chemical stressors - Fábelová, Lucia; Loffredo, Christopher A; Klánová, Jana; Hilscherová, Klára; Horvat, Milena; Tihányi, Juraj; Richterová, Denisa; Palkovičová Murínová, Ľubica; Wimmerová, Soňa; Sisto, Renata; Moleti, Arturo; Trnovec, Tomáš (Environmental research. Section A, 2019)
Hearing loss is an injury that can develop over time, and people may not even be aware of it until it becomes a severe disability. Ototoxicants are substances that may damage the inner ear by either affecting the structures in the ear itself or by affecting the nervous system. We have examined the possibility that ototoxicants may present a health hazard in association with environmental exposures, adding to existing knowledge of their proven hazards under medical therapeutic conditions or occupational activities. In addition to the already described human environmental ototoxicants, mainly organochlorines such as polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs), dibenzofurans (PCDFs), dichlorodiphenyltrichloroethane (DDT), dichlorodiphenyldichloroethylene (DDE), hexachlorocyclohexane (HCH) and hexachlorobenzene (HCB), we have examined the ubiquitous chemical stressors phthalates, bisphenol A/S/F/, PFCs, flame retardants (FRs) and cadmium for potential ototoxic properties, both as single substances or as chemical mixtures. Our literature review confirmed that these chemicals may disturb thyroid hormones homeostasis, activate aryl hydrocarbon receptor (AhR), and induce oxidative stress, which in turn may initiate a chain of events resulting in impairment of cochlea and hearing loss. With regard to auditory plasticity, diagnostics of a mixture of effects of ototoxicants, potential interactions of chemical and physical agents with effects on hearing, parallel deterioration of hearing due to chemical exposures and ageing, metabolic diseases or obesity, even using specific methods as brainstem auditory evoked potentials (BAEP) or otoacoustic emissions (OAEs) registration, may be difficult, and establishment of concentration-response relationships problematic. This paper suggests the establishment of a class of environmental oxotoxicants next to the established classes of occupational and drug ototoxicants. This will help to properly manage risks associated with human exposure to chemical stressors with ototoxic properties and adequate regulatory measures.
Keywords: látky znečišťující životní prostředí; polychlorované dibenzofurany; vnitřní ucho; Hydrocarbons, Chlorinated; Ear, Inner; polychlorované bifenyly; Environmental Pollutants; dichlordifenyldichlorethylen; polychlorované dibenzodioxiny; Humans; chlorované uhlovodíky; lidé; Dichlorodiphenyl Dichloroethylene; Dibenzofurans, Polychlorinated; Polychlorinated Dibenzodioxins; Polychlorinated Biphenyls